Simultaneous Presentation of Crohn's Disease and Takayasu Arteritis in a Teenage Patient. (November 2020) - Polyakova, Inna; Iannucci, Glen; George, Roshan; Gill, Anne; Patel, Dinesh Govind; Rouster-Stevens, Kelly
A 14-year-old female with no significant medical history presented with hypertensive urgency, in the setting of 4 to 6 weeks of diarrhea, abdominal pain, headaches, anemia, weight loss, and high blood pressures. Her evaluation revealed signs of a systemic inflammatory process that was most suspicious for inflammatory bowel disease. However, when her hypertension was evaluated with a renal Doppler ultrasound, there were signs of narrowing, stenosis, and hypoplasia that led to a diagnostic angiogram of the abdominal aorta. Full body positron emission tomography scan revealed multiple areas of stenosis and aortic thickening with enhancement compatible with Takayasu arteritis. She received prednisone, methotrexate, and infliximab with marked improvement in her clinical symptoms and inflammatory markers.